Cognitive Control Challenge Task Across the Lifespan - Politakis, Vida Ana; Slana Ozimič, Anka; Repovš, Grega (Frontiers in Psychology, 2022)
Meeting everyday challenges and responding in a goal-directed manner requires both the ability to maintain the current task set in face of distractors—stable cognitive control, and the ability to flexibly generate or switch to a new task set when environmental requirements change—flexible cognitive control. While studies show that the development varies across individual component processes supporting cognitive control, little is known about changes in complex stable and flexible cognitive control across the lifespan. In the present study, we used the newly developed Cognitive Control Challenge Task (C3T) to examine the development of complex stable and flexible cognitive control across the lifespan and to gain insight into their interdependence. A total of 340 participants (229 women, age range 8-84 years) from two samples participated in the study, in which they were asked to complete the C3T along with a series of standard tests of individual components of cognitive control. The results showed that the development of both stable and flexible complex cognitive control follows the expected inverted U-curve. In contrast, the indices of task set formation and task set switching cost increase linearly across the lifespan, suggesting that stable and flexible complex cognitive control are subserved by separable cognitive systems with different developmental trajectories. Correlations with standard cognitive tests indicate that complex cognitive control captured by the C3T engages a broad range of cognitive abilities, such as working memory and planning, and reflects global processing speed, jointly suggesting that the C3T is an effective test of complex cognitive control that has both research and diagnostic potential.